2011
DOI: 10.1097/gme.0b013e3181eeb774
|View full text |Cite
|
Sign up to set email alerts
|

Dyspareunia is associated with decreased frequency of intercourse in the menopausal transition

Abstract: Objective-Frequency of sexual intercourse declines as women enter mid-life. While partner availability and function likely play a role, menopausal symptoms, such as vaginal dryness, are also present. We examine the associations among vaginal dryness, dyspareunia, and frequency of sexual intercourse.Methods-In the second year of a longitudinal study, women completed questionnaires that included menopausal status and symptoms, participation in sexual activities, dyspareunia, marital status, and race. We used uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…The present study illustrated that less than half of women with dyspareunia decrease frequency of sexual relation than woman without dyspareunia. This result in the same line with Thomas et al [37] in their study on dyspareunia is associated with decreased frequency of intercourse in the menopausal transition and reported that women who report dyspareunia, but not vaginal dryness report less frequent intercourse. Relief of dyspareunia should be addressed to maintain sexual functioning during mid-life.…”
Section: Discussionsupporting
confidence: 89%
“…The present study illustrated that less than half of women with dyspareunia decrease frequency of sexual relation than woman without dyspareunia. This result in the same line with Thomas et al [37] in their study on dyspareunia is associated with decreased frequency of intercourse in the menopausal transition and reported that women who report dyspareunia, but not vaginal dryness report less frequent intercourse. Relief of dyspareunia should be addressed to maintain sexual functioning during mid-life.…”
Section: Discussionsupporting
confidence: 89%
“…On the one hand, frequent sexual activity may help protect postmenopausal women against developing more severe vaginal symptoms, including dyspareunia, for a variety of reasons such as improved clitoral and vulvar circulation supporting the “use it or lose it” exhortation first voiced by Masters and Johnson. 26 Alternatively, this finding may simply indicate women with more bothersome vaginal symptoms may have less frequent sexual activity precisely because they are bothered.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of hormone in menopause influence sexual desire, and this decrease is also associated with vaginal atrophy, and vaginal atrophy produces unpleasant sexual experience, thus leading to the decline of sexual frequency, further triggering a disruption in the sexual response cycle . Therefore, A few studies have applied sexual frequency, sexual desire to be indicators of sexual dysfunction . Compared to structural questionnaires, sexual frequency is easy to be remembered by midlife women, and sexual desire can be easily and quickly obtained by the subjective responses, which could be simple tools for evaluating sexual function for middle‐aged women.…”
Section: Introductionmentioning
confidence: 99%